Work and processes of mental illness: an analysis of the absences of public servants in the city of Santa Maria/RS - Marques, Marcia Goularte; Costa, Diogo Faria Corrêa da (Disciplinarum Scientia | Saúde, 2025)
This article discusses the relationship between work and mental illness among civil servants in Santa Maria/RS. The general objective was to understand the relationships between work and mental illness based on the analysis of absences of public servants. The specific objectives were: a) to carry out a survey of absences due to mental illness; b) to analyze the data obtained to current issues in the world of work; c) to discuss proposals for the prevention of mental health. As a method, a documentary survey of sick leave was carried out, looking for the information: diagnoses, departments of employment, gender and length of leave. A narrative review of the literature was then carried out, relating the survey to current literature. As a result, between 2021 and 2022, 171 civil servants were absent from their jobs, predominantly female health professionals, with emotional issues such as overload, exhaustion and stress standing out. In conclusion, the study pointed to the importance of defensive strategies in the face of psychological distress and the need for greater knowledge about the causal link between work and psychological distress in order to establish preventive and promotional measures for workers’ health.